(untitled) (REMUNOM, 2025)
The issue of mental well-being in professional settings has become a growing topic of importance due to shifts in society, economy, and technology that directly influence employees. This piece explores the key elements that affect mental health at work, including excessive workload, authoritarian management styles, workplace culture, and constant connectivity. It also examines the effects of mental health disorders on both individuals and organizations, such as psychological symptoms, decreased efficiency, and harm to the organization’s reputation. Lastly, it outlines methods for enhancing mental health based on recent research, emphasizing the significance of support systems, attentive listening, leadership development, and preventative measures. Mental health is recognized as both a strategic and moral resource, vital for fostering a healthy and sustainable work environment.